If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x-8)-4=4(x-2)
We move all terms to the left:
4(3x-8)-4-(4(x-2))=0
We multiply parentheses
12x-(4(x-2))-32-4=0
We calculate terms in parentheses: -(4(x-2)), so:We add all the numbers together, and all the variables
4(x-2)
We multiply parentheses
4x-8
Back to the equation:
-(4x-8)
12x-(4x-8)-36=0
We get rid of parentheses
12x-4x+8-36=0
We add all the numbers together, and all the variables
8x-28=0
We move all terms containing x to the left, all other terms to the right
8x=28
x=28/8
x=3+1/2
| 4/10x=30 | | 1296=6^2x+1 | | (1.5)^2=15w | | .83x=3 | | (3p)(p-5)-2(p+3)=p(p+3) | | X+36+x+102=124 | | 3x^2+10x-57=0 | | 5s+3=2 | | b/2+13=-4 | | x/56=14/100 | | 32-3x=40 | | 16x^2+2=12x | | 4+x=-36 | | 2-5x=-7x+20 | | x+3^x=8 | | 4x-4+26x+4=180 | | 3|g+8|+2=53 | | -30p=6 | | 5.8=-1+x | | -2+5(1–5x)=x-5(6x+1) | | 200+2x+3x=360 | | 4(u+3)+7=47 | | 131+x+x+41=150 | | 11x+50=6x+15 | | 200+2x+3×=360 | | 2(b+1)=20 | | s/5+4=19 | | 3/5x+9/10=-1/5x+23/10 | | 94+x+x+36=122 | | 2x^2=10x-37 | | s5+4=19 | | 5(x-5)=-44 |